Shaping 90 wt% NanoMOFs into Robust Multifunctional Aerogels Using Tailored Bio‐Based Nanofibrils. Issue 38 (16th August 2022) - Rostami, Jowan; Benselfelt, Tobias; Maddalena, Lorenza; Avci, Civan; Sellman, Farhiya Alex; Cinar Ciftci, Goksu; Larsson, Per A.; Carosio, Federico; Akhtar, Farid; Tian, Weiqian; Wågberg, Lars
Abstract: Metal–organic frameworks (MOFs) are hybrid porous crystalline networks with tunable chemical and structural properties. However, their excellent potential is limited in practical applications by their hard‐to‐shape powder form, making it challenging to assemble MOFs into macroscopic composites with mechanical integrity. While a binder matrix enables hybrid materials, such materials have a limited MOF content and thus limited functionality. To overcome this challenge, nanoMOFs are combined with tailored same‐charge high‐aspect‐ratio cellulose nanofibrils (CNFs) to manufacture robust, wet‐stable, and multifunctional MOF‐based aerogels with 90 wt% nanoMOF loading. The porous aerogel architectures show excellent potential for practical applications such as efficient water purification, CO2 and CH4 gas adsorption and separation, and fire‐safe insulation. Moreover, a one‐step carbonization process enables these aerogels as effective structural energy‐storage electrodes. This work exhibits the unique ability of high‐aspect‐ratio CNFs to bind large amounts of nanoMOFs in structured materials with outstanding mechanical integrity—a quality that is preserved even after carbonization. The demonstrated process is simple and fully discloses the intrinsic potential of the nanoMOFs, resulting in synergetic properties not found in the components alone, thus paving the way for MOFs in macroscopic multifunctional composites. Abstract : A novel sustainable material strategy is reported to fabricate wet‐stable, mechanically robust, and elastic multifunctional nanoMOF‐CNF aerogels with the highest reported nanoMOF loading of 90 wt%, enabled by high‐aspect‐ratio cationic CNFs. The carbonized and non‐carbonized aerogels are effectively demonstrated for water purification, CO2 and CH4 gas storage and separation, flame retardancy, and energy storage.